PHARMACEUTICAL INTERACTION BETWEEN CYTOSTATIC DRUGS AND NACL 0,9% AND DEXTROSE 5% INFUSION - Khotib, Junaidi; Wara Shinta, Dewi; Karsono, Surjiani; Zubaida, Betty; Samirah; Aryani, Toetik; Kurniawan, Muhammad Arif; Suprapti, Budi (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective. Pharmaceutical interaction between cytostatic drugs and its infusion fluids and packaging materials may cause therapy failure and reduce its cytostatic potential. Therefore, several tests on pharmaceutical interaction between several cytostatic drugs which are most commonly used in clinics and its infusion fluids need to be done. Methods. Some cytostatic drugs (such as cyslophosphamide, 5-fluorouracyl, cisplatin, and paclitaxel) are dissolved in certain concentration of NaCl 0.9% or Dextrose 5% infusion solution. Then, the solutions are incubated at room temperature and protected from sunlight. On the 0th hour (initial condition), 2nd, 4th, 8th, 12th, and 24th hour visual observations, pH measurement, and content measurement are performed. Results. Based on visual observations, it is indicated that there is no change in color, clarity, and particles of all solutions. At pH measurement, obtained changes in pH of cytostatic solution, which is still within the tolerable range of injection preparation (pH 4-10) and on active compounds stability range. Meanwhile, based on change of cytostatic concentration in each solution, it is indicated that there is no significant difference after 24-hour observation. Conclusion. Cytostatic drugs dissolved in NaCl 0.9% or Dextrose 5% infusion remained stable in terms of clarity, pH, and concentration level. Â Â Keywords: cyclophosphamide, 5-fluorouracyl, cisplatin, paclitaxel, pharmaceutical interaction.